2013
DOI: 10.5505/adlitip.2013.54154
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Cardiac Conduction System In Sudden Deaths

Abstract: Objective:In this study, revealing the regional characteristics of the cardiac conduction system pathologies in sudden death cases is aimed. Besides, this is the first study of Adana region forensic cases related to the cardiac conduction system pathologies. Methods:Twenty seven cases of sudden unexpected death and 4 cases with known causes of death as a control group have been included in the study. Samples from sinoatrial node and atrioventicular node were taken in total 31 cases. Samples were evaluated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 25 publications
(24 reference statements)
3
7
0
Order By: Relevance
“…In present study males were 85.21%, while 14.78% cases were females (Figure 1). The male dominance was reported by other authors Bora Ozdemir et al 18 reported 73% male and 27% female, Ramazan Karanfil et al 19 reported 74% male and 26% female and Thomas AC, Knapman PA et al 20 reported ischemic heart disease accounted 59% of the sudden deaths in 65% men and 41% women.…”
Section: Resultsmentioning
confidence: 55%
“…In present study males were 85.21%, while 14.78% cases were females (Figure 1). The male dominance was reported by other authors Bora Ozdemir et al 18 reported 73% male and 27% female, Ramazan Karanfil et al 19 reported 74% male and 26% female and Thomas AC, Knapman PA et al 20 reported ischemic heart disease accounted 59% of the sudden deaths in 65% men and 41% women.…”
Section: Resultsmentioning
confidence: 55%
“…Similar findings were reported by Ramazan Karanfil et al, 17-78 years and Chandrakala Joshi 41-60years. 2,4 This shows that age is a powerful risk factor for heart disease. The development of atherosclerosis increases markedly with age up to an age of about 65.…”
Section: Discussionmentioning
confidence: 98%
“…Similar findings were reported by Ramazan Karanfil et al, 75%, stavroula A et al, 77% and Chandrakala Joshi 64%. 2,4,5 Calcification was present in 34(53.3%) cases and thrombus in 4(5.3%) cases. Similarly thrombosis was reported in 4.8% cases by Bora Ozdemir et al 6 Plaque calcification is found more frequently in advanced lesions, it may also occur in small amounts in earlier lesions, which appear in 2 nd and third decade of life.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations